Tissue Factor-bearing MPs and the risk of venous thrombosis in cancer patients: A meta-analysis - Chan-juan Cui (Nature Portfolio, 2018)
Abstract Cancer patients with Tissue Factor (TF)-bearing MPs have been presented association with increased risk of venous thromboembolism (VTE), but results of these studies have not been consistent. We aimed to conduct a meta-analysis to assess the relationship between TF-bearing MPs and risk of VTE in patients with cancer. PubMed, Web of Science and EMBASE Databases were systematically retrieved up to1th June 2017. Two case-control studies and four cohort studies met the entry requirements in this analysis. The summary odd ratio (OR) were estimated by a random effect model. The overall OR was 1.76 (95% CI: 1.21–2.56, I2 = 62.0%). The OR of case-control studies was 3.41 (95% CI: 1.45–8.02, I2 = 0.0%) and that of cohort studies was1.53 (95% CI: 1.05–2.24, I2 = 66.1%). The association between TF-bearing MPs and the risk of VTE in cancer patients was found in this meta-analysis. Publication bias testing and sensitivity subgroup analysis suggested that results of this meta-analysis were robustness. In conclusion, TF-bearing MPs were associated with increased risk of VTE in patients with cancer. Whereas, more well-designed studies and more comprehensive adjustments for confounders in further studies are warranted to affirm the association.